2022
DOI: 10.3390/su14127356
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ground Thermal Properties of Shallow Coaxial Borehole Heat Exchanger Using an Improved Parameter Estimation Method

Abstract: Ground thermal properties are prerequisites for designing the size of borehole heat exchanger. In this study, a 3D heat transfer model is developed to simulate the thermal response test (TRT) of shallow coaxial borehole heat exchanger (SCBHE), and effects of ground thermal properties on the slope of the mean value of inlet and outlet fluid temperatures are studied. The results show that the slope is strongly affected by ground thermal conductivity and is slightly affected by ground thermal capacity, and that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Mogensen [22] reported values λ g = 2.69 W/m K and R b = 0.1266 K/W m, while Reuss [19] reported that λ g = 2.2 W/m K and ρc = 2.8 MJ/m 3 K. Gehlin [20] indicated that the thermal conductivity of the ground when a borehole is filled with grout is 3.45 W/m K, while it is 3.62 W/m K when filled with water. In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data.…”
Section: Introductionmentioning
confidence: 99%
“…Mogensen [22] reported values λ g = 2.69 W/m K and R b = 0.1266 K/W m, while Reuss [19] reported that λ g = 2.2 W/m K and ρc = 2.8 MJ/m 3 K. Gehlin [20] indicated that the thermal conductivity of the ground when a borehole is filled with grout is 3.45 W/m K, while it is 3.62 W/m K when filled with water. In recent years, studies in [23][24][25][26][27][28][29][30][31] showed improvements and applications of the TRT procedure for evaluating BHE efficiency. Luo et al [23] studied the influence of an unstable power input on the unacceptable errors of the TRT measured data.…”
Section: Introductionmentioning
confidence: 99%